Riba in the Sharia: Its Conceptual Framework and Implications for Contractual Practices: الرِّبَا فِي الشَّرِيعَةِ: الإِطَارُ المَفَاهِيمِيّ وَآثَارُهُ عَلَى المُعَامَلَاتِ العَقْدِيَّةِ - Amel Saib; Mariam Elbanna; Muthoifin (Walidem Institute and Publishing (WIP), 2025)
Objective: This research aims to discuss the issue of legal disputes related to riba as a barrier to the acceptance of financial transactions in Islam. Riba, which undermines the principles of justice and equality, is prohibited to maintain the integrity of financial transactions and the purity of intention in economic activities. Theoretical framework: The theoretical framework of this study is based on Sharia principles that emphasize justice, transparency, and social welfare as the foundation of Islamic law in financial transactions. This study examines the concept of riba and its impact on contracts from legal and ethical perspectives. Literature Review: The literature reviewed includes normative, theological, and fiqh studies relevant to elucidating the impact of riba on the validity of contracts in Islamic law. Methods: The research methodology is inductive and qualitative, employing normative, theological, and fiqh-based approaches. This study strives to explain the principles underlying the prohibition of riba and to offer practical guidance for Muslims to ensure that their financial transactions comply with Sharia. Results: The research findings indicate that the elimination of riba in financial transactions is crucial for creating a fair and ethical financial system, thereby protecting individuals and ensuring that their transactions are safer and Sharia-compliant. The prohibition of riba is not merely a legal rule but also reflects the broader objectives of Sharia in promoting social welfare and ethical behavior. Implications: The implications of this research include the development of a legal framework and practical guidelines that can assist Muslims in conducting financial transactions that are legally valid and aligned with Islamic values. Novelty: The novelty of this research lies in its holistic approach, combining legal, theological, and fiqh analyses to clarify the concept of riba and its impact on the validity of contracts in Islam. This study makes a significant contribution by linking the legal and ethical aspects of financial transactions in accordance with Sharia.